2018
DOI: 10.26034/tranel.2018.2892
|View full text |Cite
|
Sign up to set email alerts
|

Is the power of weak ties universal? A cross-cultural comparison of social interaction in Argentina and Canada

Abstract: Although we interact with a wide range of people on a daily basis, the social psychological literature has primarily focused on interactions with close friends and family (i.e. strong ties). Recent research carried out on Canadian students suggests emotional benefits to interacting with acquaintances (i.e. weak social ties). The present study investigates whether this 'weak tie effect' holds in non-Western cultures, using a Latin American sample to broaden our understanding of collectivism. Participants report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…In a followup study, however, the effects of weak-tie interactions were not replicated in community samples in Toronto and Argentina. For both samples, wellbeing did not relate to either weak ties or strong ties (Tilston & Sandstrom, 2018). Thus, in some contexts, having multiple interactions, even if the interaction is of low quality, may be psychologically advantageous for individuals (Sandstrom & Dunn, 2014), but in others, it may not be (Tilston & Sandstrom, 2018).…”
Section: Is There a Relation Between The Quality Of The Conversations...mentioning
confidence: 76%
See 1 more Smart Citation
“…In a followup study, however, the effects of weak-tie interactions were not replicated in community samples in Toronto and Argentina. For both samples, wellbeing did not relate to either weak ties or strong ties (Tilston & Sandstrom, 2018). Thus, in some contexts, having multiple interactions, even if the interaction is of low quality, may be psychologically advantageous for individuals (Sandstrom & Dunn, 2014), but in others, it may not be (Tilston & Sandstrom, 2018).…”
Section: Is There a Relation Between The Quality Of The Conversations...mentioning
confidence: 76%
“…Our analyses here again are exploratory. This is because the association between the quality of the conversations and wellbeing as a function of cultural background is limited and the evidence reviewed also shows distinct results: While there is evidence that substantive conversations are beneficial for individuals (Mehl et al, 2010;Milek et al, 2018), daily weak-tie interactions are also found to be related to wellbeing (Sandstrom & Dunn, 2014), yet this was not replicated in community samples (Tilston & Sandstrom, 2018).…”
Section: Goals and Study Overviewmentioning
confidence: 99%
“…That said, the value of positive interactions with unfamiliar or weaker social ties should not be underestimated. Indeed, interactions with weak social ties capture attentional resources (Weng et al, 2018), have benefits for social capital and well-being (DeAndrea et al, 2012; Granovetter, 1973; Liu & Yeo, 2021; Sandstrom & Dunn, 2014; Sutcliffe et al, 2018; Tilston & Sandstrom, 2018; Walsworth et al, 2021), and serve as the impetus for developing closer relationships both in person and online (Ostertag & Ortiz, 2017; Standlee, 2019). Broader and more public sharing and subsequent positive feedback may also strengthen weak social ties and form the foundation for deeper relationships in private spaces (Sas et al, 2009).…”
Section: Discussionmentioning
confidence: 99%